Scanning-fluorescence Reader Based on Embedded System - Zhonglong Zhao; Xiaoping Min; Shengxiang Ge; Ningshao Xia (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
To measure the concentration of C-reactive protein (CRP) in serum, a portable, scanning-fluorescence reader based on time-resolved fluoroimmunoassays was developed. The scanning-fluorescence reader integrates with the AD7707 converter, which performs at a high accuracy. The photosensitive diode acts as the photoelectric conversion device, an optical module based on optical fibers, which is able to concentrate the excitation light from an LED into a line-shape beam, was designed to sendand receive the optical signal. The device subsequently addresses waveform data using a gradient, smoothing, and binarization method. When the device measures the CRP fluorescence test strip, the results exhibited a good linearity (0.99998) and the CVs (coefficient of variation) were below 5%, which indicate high accuracy. At the same time the system is low cost and small size.